Circular RNA_0037128 aggravates high glucose-induced damage in HK-2 cells via regulation of microRNA-497-5p/nuclear factor of activated T cells 5 axis. Issue 2 (20th December 2021) - Feng, Tao; Li, Weifang; Li, Tianyi; Jiao, Wenjun; Chen, Sufang
ABSTRACT: Circular RNAs (CircRNAs) were reported to play vital roles in the progression of DN. Herein, the action of circular RNA_0037128 (circ_0037128) was investigated in DN. The level of circ_0037128, microRNA-497-5p (miR-497-5p) and nuclear factor of activated T cells 5 (NFAT5) was determined using quantitative real-time polymerase chain reaction (qRT-PCR). The feature of circ_0037128 was tested by RNase R and Actinomycin D treatment assays. Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2ʹ-deoxyuridine (EdU) staining assays were conducted to evaluate the proliferation ability. The relative protein expression was determined via Western blot analysis. Levels of the inflammatory cytokines, like tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6), were assessed by enzyme-linked immunosorbent assay (ELISA). Reactive oxygen species (ROS) production, lactate dehydrogenase (LDH) and superoxide dismutase (SOD) activity were determined by the matched kits. Dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were conducted for evaluating the correlation between miR-497-5p and circ_0037128 or NFAT5. Circ_0037128 and NFAT5 were enhanced, while miR-497-5p was weakened in kidney tissues of DN patients and high glucose (HG)-cultured HK-2 cells. Circ_0037128 inhibition bated HG-caused inhibition effect on cell proliferation and promotion effects on oxidative stress, inflammation and fibrosis in HK-2 cells. Moreover, circ_0037128 knockdown alleviated HG-caused cell damage via regulating miR-497-5p. In addition, NFAT5 overexpression could reverse the influence of miR-497-5p on HG-induced injury in HK-2 cells. Mechanically, circ_0037128 sponged miR-497-5p to modulate NFAT5. Circ_0037128 downregulation could mitigate HG-stimulated cell damage via regulating the miR-497-5p/NFAT5 axis in HK-2 cells in vitro, providing a possible therapy target for DN.